KONTRIBUSI KYAI AGENG MUHAMMAD BESARI DALAM AKULTURASI DAKWAH ISLAM DI PONOROGO JAWA TIMUR - Alfiana Yuniar Rahmawati (Jurnal Al-Hikmah: Jurnal Dakwah, 2021)
ABSTRACT The spread of Islamic teachings in Ponorogo can not be separated from the role of a kyai. Kyai is domiciled as a central figure in the life system of the community and pesantren. As a promoter in Islamic civilization, kyai figure is faced with socio-cultural reality and social change in society. Da'wah islam becomes a challenge that must be faced because the religion of Islam comes as a religion of renewal of the religion of ancestors who have been ingrained in the environment. The role of Ageng Besari kyai in spreading Islam in Ponorogo can be traced from three important aspects, namely the field of religion, social and political fields. Efforts to spread Islam by Kyai Ageng Besari can be felt throughout the ponorogo region in the form of cultural acculturation as well as historical relics such as mosques, tombs, religious traditions, to the emergence of large pesantren-pesantren that still exist today. Kyai Besari is famous as a great teacher on the island of Java because of his success in educating his students into big people and became a mainstay of ponorogo society as Warok Ponorogo who is famous for his magic.